Aplikasi Sistem Rangka Manusia Untuk Pembelajaran Biologi Berbasis Augmented Reality - Hanum Salsabila Zakiyah; Wahyu Sri Utami (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The anatomy learning process on human skeletal system material utilizes media as a learning aid. Learning media is a method used by teachers and students to communicate during the learning process. Communication in learning can run optimally with the help of means of delivering messages or media. Based on this explanation, this research aims to develop human skeletal system applications for learning media using augmented reality technology. Augmented reality learning media can visualize abstract concepts for understanding and structure of an object model. This research uses augmented reality technology with marker-based tracking method. The development method used for this application is MDLC (Multimedia Development Life Cycle). Testing uses several kinds of android smartphones and functional testing of applications in accordance with the needs. With the development of this android-based application is expected to increase knowledge and interest in learning students for learning the human skeletal system